The progression of male 100 m sprinting with a lower-limb amputation 1976-2012 - Dyer, D. (Sports, 2015)
Sprinting with a lower-limb amputation over 100 m has taken place in the Paralympic Games for over three decades. The aim of this paper is to statistically evaluate the performances and participation levels of such athletes during this period. The level of performance improvement over a 36-year period was proposed to be significantly greater than the able-bodied equivalent. Coupled with this, a major spike in amputee running performance improvement was shown to occur from 1984-1988. This supports previously recorded accounts of a major technological change being made at this time. Finally, whilst the average performance of the medallists has increased consistently over the 36-year history, the overall participation in the event fell significantly after 1988 and did not recover until 2012.